Dos nuevas especies de Commelina (Commelinaceae) mexicanas - Lopez-Ferrari, Ana Rosa; Espejo Serna, Adolfo; Ceja Romero, Jacqueline (Instituto de Ecología, A.C., 1997)
Commelina nivea López-Ferrari, Espejo et Ceja, and Commelina rzedowskii López-Ferrari, Espejo et Ceja, two white flowered species are described and illustrated in this paper. The former is known only from Las Adjuntas, municipio of Pueblo Nuevo in the state of Durango and the other was collected in the neighborhood of Tenería, municipio of Tejupilco in the state of México.